(untitled) (Eurasian Research Bulletin, 2022)
Interpreting the phraseological unit on the basis of their relation perceptions shaped by stereotypes, reflecting the people’s mentality, we thus reveal their cultural and national sense and character, which is the content of the national and cultural connotations.